Sociological critique of men’s capital according to Pierre Bourdieu’s theory of types of capital in Suvashun’s novel - Zabbah, Mahmoud; Firouzimoghaddam, Mahmoud; Alavimoghaddam, Mehyar (Cadernos de Educação Tecnologia e Sociedade, 2021)
In the following article we seek to critique the sociology of contemporary Persian novels, based on the theory of the various types of capital of the French sociologist Pierre Bourdieu. Bourdieu generalizes the Marxist analysis of economic capital to a variety of cultural, social, and symbolic exchanges. He believes that these capabilities are forms of capital because they contribute to the purchasing power of different situations. This multifaceted concept of capital makes it possible to provide a better picture of the structure, order of relationships, and dependencies of social space. Based on this, we examine the four types of capital of the male characters of Simin Daneshvar's novel "Suvashun" and we showed that; what methods do men choose based on their behavioral mood to produce and maintain capital? And what prevents them from gaining power? The sociological study of men's capital in Suvashun's novel deals with the position of male characters in various fields and it opens up various ways for them to earn or lose capital.